2022
DOI: 10.1093/hmg/ddac088
|View full text |Cite
|
Sign up to set email alerts
|

Role of non-coding RNAs on liver metabolism and NAFLD pathogenesis

Abstract: Obesity and type 2 diabetes are major contributors to the growing prevalence of non-alcoholic fatty liver disease (NAFLD), a chronic liver condition characterized by accumulation of fat in individuals without a significant amount of alcohol intake. The NAFLD spectrum ranges from simple steatosis (early stages, known as NAFL), to non-alcoholic steatohepatitis (NASH), which can progress to fibrosis and cirrhosis or hepatocellular carcinoma. Obesity, type 2 diabetes, and NAFLD are strongly associated with insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…The limitations of the study are acknowledged as follows: Our study showed the development of NAFLD and insulin resistance in HFD model, but we haven’t performed a whole transcriptomic sequencing on liver cells in HFD mice to investigate the associated pathways. Given that liver can regulate β-cell function through various metabolic processes and non-coding RNAs [ 59 , 60 ], conducting liver RNA sequencing simultaneously could offer additional valuable insights into the interplay between the liver and the islets. Furthermore, the predicted targets of DE miRNAs should be further confirmed using methods such as dual luciferase reporter assays, RNA-binding protein immunoprecipitation, and validation at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the study are acknowledged as follows: Our study showed the development of NAFLD and insulin resistance in HFD model, but we haven’t performed a whole transcriptomic sequencing on liver cells in HFD mice to investigate the associated pathways. Given that liver can regulate β-cell function through various metabolic processes and non-coding RNAs [ 59 , 60 ], conducting liver RNA sequencing simultaneously could offer additional valuable insights into the interplay between the liver and the islets. Furthermore, the predicted targets of DE miRNAs should be further confirmed using methods such as dual luciferase reporter assays, RNA-binding protein immunoprecipitation, and validation at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research studies have proved that miRNAs play a significant regulatory role in the liver glycolipid metabolism, 23 but the mechanism of miRNAs in fluoride-induced hepatic glycolipid metabolism disorders is still unclear. Therefore, this study used the miRNA-seq and mRNA-seq to screen the key miRNAs and mRNAs and revealed the regulatory mechanism in fluoride-induced liver glycolipid metabolism disorders.…”
Section: ■ Discussionmentioning
confidence: 99%
“…While a dysregulated lncRNA profile seems to be involved in the pathogenesis of diet-induced metabolic diseases such as MASLD [ 54 , 55 ], recent evidence suggests that lncRNAs also contribute to the regulation of insulin signaling and glucose metabolism in several tissues and to the pathogenesis of insulin resistance (reviewed in detail by others [ 78 , 79 ]). By controlling pathways of glucose metabolism, the liver has a major role in the control of glucose homeostasis [ 80 ], and insulin resistance seems to be associated with an increase in hepatic glucose output, lipogenesis, and VLDL secretion, leading to a combination of hyperglycemia and hypertriglyceridemia [ 81 ].…”
Section: Lncrna and Glucose Metabolismmentioning
confidence: 99%